Pengaruh Pemberian Elisitor Homogenat Jamur Pythium aphanidermatum (Edson) Fitzp. terhadap Kandungan Ajmalisin dalam Kultur Akar Catharantus roseus (L) G. Don - Mukarlina Mukarlina; Rizkita Rachmi Esyanti; Arbayah Hamonangan Siregar (Institut Teknologi Bandung, 2006)
An experiment to study the effect of elicitor from Pythium aphanidermatum (Edson) Fitzp. on ajmalicine content of Catharanthus roseus (L) G. Don. root culture has been conducted. The C. roseus root culture in Zenk medium (1977) with the the addition of 10-7 M of napthalene acetic acid (NAA) and 10-7 M of benzylaminopurine (BAP) as growth factors was elicited with autoclaved P. aphanidermatum homogenate at concentrations of 0.05, 0.5, 1.0 and 50 mg DW/mL, then harvested at 18, 24, 36, 48, and 72 h after elicitation. The ajmalicine content was analyzed qualitatively and quantitatively by HPLC (High Pressure Liquid Chromatography) connected to chromatopack CR-7A plus. The result showed that ajmalicine content was influenced significantly by the concentration of elicitor and harvesting time. The highest ajmalicine content on the roots i.e. 165.6 Â± 1.1 Î¼g/g DW with the increment percentage of 181,6% was obtained by addition of 5.0 mg DW/mL of elicitor for 24 h, while on the media, the highest ajmalicine content i.e. 291.5 Â± 0.9 mg DW/mL with the increment percentage of 306,5% was obtained by addition of 5.0 mg DW/mL elicitor for 36 hours. These results indicated that elicitation might be responsible for the higher ajmalicine content in the media compared to its accumulation in the root.